Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Chen, Ye-Hui; Xu, Yi-Cheng; Lin, Ting-Ting; Chen, Hang; Dong, Ru-Nan; Cai, Feng-Ping; Ke, Zhi-Bin; Chen, Jia-Yin; Wei, Yong; Zheng, Qing-Shui; Xue, Xue-Yi; Xu, Ning (Inflammation research, 2023)
Objective and design Post-traumatic urethral stricture is a clinical challenge for both patients and clinicians. Targeting glutamine metabolism to suppress excessive activation of urethral fibroblasts (UFBs) is assumed to be a potent and attractive strategy for preventing urethral scarring and stricture. Material or subjects In cellular experiments, we explored whether glutaminolysis meets the bioenergetic and biosynthetic demands of quiescent UFBs converted into myofibroblasts. At the same time, we examined the specific effects of M2-polarized macrophages on glutaminolysis and activation of UFBs, as well as the mechanism of intercellular signaling. In addition, findings were further verified in vivo in New Zealand rabbits. Results It revealed that glutamine deprivation or knockdown of glutaminase 1 (GLS1) significantly inhibited UFB activation, proliferation, biosynthesis, and energy metabolism; however, these effects were rescued by cell-permeable dimethyl α-ketoglutarate. Moreover, we found that exosomal miR-381 derived from M2-polarized macrophages could be ingested by UFBs and inhibited GLS1-dependent glutaminolysis, thereby preventing excessive activation of UFBs. Mechanistically, miR-381 directly targets the 3′UTR of Yes-associated protein (YAP) mRNA to reduce its stability at the transcriptional level, ultimately downregulating expression of YAP, and GLS1. In vivo experiments revealed that treatment with either verteporfin or exosomes derived from M2-polarized macrophages significantly reduced urethral stricture in New Zealand rabbits after urethral trauma. Conclusion Collectively, this study demonstrates that exosomal miR-381 from M2-polarized macrophages reduces myofibroblast formation of UFBs and urethral scarring and stricture by inhibiting YAP/GLS1-dependent glutaminolysis.